Implementation of Fuzzy Tsukamoto Method in Analyze Science Teacher’s Technological Pedagogical Content Knowledge - Safriana Safriana*; Zahratul Fitri; Fajrul Wahdi Ginting (Universitas Syiah Kuala, 2023)
Improving the quality of teachers is the toughest challenge as well as a strategic effort that must be done to improve the quality of education in Indonesia, especially Aceh. The qualifications of a teacher are determined by the ability of technological pedagogical content knowledge (TPACK). The ability of teachers' TPACK is an important factor that determines the success of improving the quality of education in an area. The purpose of this study was to determine the level of TPACK ability of science teachers in Lhokseumawe City using the fuzzy t.,sukamoto method in evaluating teacher learning. Based on the results of the study, it can be supposed that the Fuzzy Tsukamoto method can be used to determine the level of TPACK ability of science teachers in Lhokseumawe City. Using a random sample of 10 (ten) data records that 5 (five) records have a degree of very good, 4 (four) records have a degree of good and 1 (one) record has a degree of very bad. Teachers in Lhokseumawe City have a very good level of TPACK